Analysis of spontaneously reported adverse drug reactions to pharmacovigilance cell of a tertiary care hospital - Patel, Kaksha J.; Panchasara, Ashwin K.; Barvaliya, Manish J.; Tripathi, C. B. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The objective of the study was to study the clinical patterns, causality and severity of adverse drug reactions in a tertiary care hospital. Methods: Total 131 ADR forms were collected from January 2012 to December 2012 and evaluated. Patient’s characteristics, ADR and drug characteristics, causality, severity and preventability of collected ADR were analyzed. Results: Total 131 ADR forms were evaluated. Male patient experiencing ADR were more (73, 55.7%) than female (58, 44.2%). Adult patients (12-60 years) experienced 110 (84%) ADR followed by pediatric patients (< 12 years) 11 (8.4%) and geriatric patients (>60 years) 10 (7.63%). Antimicrobial were the most common group of drugs responsible for ADR followed by NSAIDs and antipsychotic group. Conclusions: Present study shows lack of awareness among health care professionals for reporting of an ADR. Training and collaboration of health care professionals are needed for improvement in ADR reporting. Appropriate feedback from ADR reporting will help in selection of drug and promotes safer use of drugs.